2011
DOI: 10.1002/star.201000123
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high‐pressure microfluidization on the structure of cassava starch granule

Abstract: Microfluidization has been applied to modify starch granules. The study was conducted to investigate the effect of microfluidization on the structure and thermal properties of cassava starch–water suspension (20% w/w). The means of optical microscopy, SEM, FTIR spectroscopy, XRD, and DSC were applied to analyze the changes in microstructure, crystallinity, and thermal property. Microscopy observations revealed that native starch granules were oval, round, and truncated in shape. After the microfluidization tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
42
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 51 publications
11
42
0
Order By: Relevance
“…Therefore, the partial gelatinization of TS could lead to the increase in particle size due to the presence of aggregates. Similar results were also obtained by Kasemwong et al (2011) who reported that the granule size of cassava starch increased with increasing microfluidization pressure, which may be attribute to the partial gelatinization of cassava starch. Qiu, Li, Chen, Liu, and Yin (2014) also suggested that the particle size distribution curve of homogenized wheat starch granules shifted to a higher value compared to native starch.…”
Section: Particle Size Analysissupporting
confidence: 91%
See 2 more Smart Citations
“…Therefore, the partial gelatinization of TS could lead to the increase in particle size due to the presence of aggregates. Similar results were also obtained by Kasemwong et al (2011) who reported that the granule size of cassava starch increased with increasing microfluidization pressure, which may be attribute to the partial gelatinization of cassava starch. Qiu, Li, Chen, Liu, and Yin (2014) also suggested that the particle size distribution curve of homogenized wheat starch granules shifted to a higher value compared to native starch.…”
Section: Particle Size Analysissupporting
confidence: 91%
“…Similar results were also observed with maize amylose and cassava starches (Che et al, 2007;Tu et al, 2013). However, different results were found by Kasemwong et al (2011) who reported that the shapes of cassava starch granules remained unaltered but the originally smooth surfaces of some granules became rough after treated by DHPM.…”
Section: Semsupporting
confidence: 85%
See 1 more Smart Citation
“…The smaller the particle is, the greater the aggregation trend is. [30] also reported the granule size of starch was increased with the increase in homogenizing and microfluidization pressure, respectively. The effect of microfluidization is possibly the results of a combination of the disruption of the semicrystalline structure followed by hydration and radial swelling of the starch granules, when the starch-water suspension was put through the microfluidizer [30].…”
Section: Morphological Characteristics 321 Granule Size Analysismentioning
confidence: 93%
“…The results showed that the resistant starch treated with microfluidization contained increased viscosity and water-holding properties. Kasemwong et al [30] studied the effect of microfluidization on the structure and thermal properties of cassava starch-water suspension (20% w/w). The results indicated that DHPM process induced the gelatinization of cassava starch.…”
Section: Introductionmentioning
confidence: 99%